2014
DOI: 10.1021/am404624z
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanowhiskers and Fiber Alignment Greatly Improve Mechanical Properties of Electrospun Prolamin Protein Fibers

Abstract: Electrospun fibers from natural polymers must possess appropriate mechanical properties if they are to be functional in numerous applications. In this research, two convenient physical approaches were applied to reinforce the assembled hordein/zein electrospun nanofabrics: incorporation of surface-modified cellulose nanowhiskers (SCN) and fiber alignment. The mechanical properties and stability of the modified fibers were tested in relation to fiber morphology and structure as characterized by scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…The authors observed that the fibers were pepsin resistant and stable in simulated gastric fluid (SGF), whereas they could be digested in a simulated intestinal fluid (SIF) to gradually release the incorporated compounds where they are normally absorbed [ 112 ]. In a further work [ 113 ], the same research group obtained the same material applying two physical approaches: (i) incorporation of surface-modified cellulose nanowhiskers (SCNs); and (ii) fiber alignment, to reinforce the assembled hordein/zein electrospun nanofabrics. The stability and mechanical properties of the modified fibers were evaluated in relation to the fiber morphology, and the structure was characterized by SEM, TEM, FTIR and Raman spectroscopy.…”
Section: Biomedical Applications Of Zein-based Materialsmentioning
confidence: 99%
“…The authors observed that the fibers were pepsin resistant and stable in simulated gastric fluid (SGF), whereas they could be digested in a simulated intestinal fluid (SIF) to gradually release the incorporated compounds where they are normally absorbed [ 112 ]. In a further work [ 113 ], the same research group obtained the same material applying two physical approaches: (i) incorporation of surface-modified cellulose nanowhiskers (SCNs); and (ii) fiber alignment, to reinforce the assembled hordein/zein electrospun nanofabrics. The stability and mechanical properties of the modified fibers were evaluated in relation to the fiber morphology, and the structure was characterized by SEM, TEM, FTIR and Raman spectroscopy.…”
Section: Biomedical Applications Of Zein-based Materialsmentioning
confidence: 99%
“…One was the strong interactions, such as hydrogen bonds, between nanocrystals and cellulose matrix. Another was the increased alignment of cellulose chains in the fiber direction . Further increase of nanocrystal content would lead to the decrease of σ b .…”
Section: Resultsmentioning
confidence: 99%
“…CENC have great strength and axial elastic modulus, large specific surface area, high aspect ratio, low density, and a large number of hydroxyl side groups on the surface . Because of these unique properties, CENC have been used as reinforcements to improve the mechanical properties of poly(vinyl alcohol) (PVA) films, prolamin protein fibers, cellulose acetate film, bio‐based polyurethane, poly(lactic acid) composites, cellulose composites, acrylic composites, and other materials …”
Section: Introductionmentioning
confidence: 99%
“…The addition of cationically modified (using phenyltrimethylammonium chloride) CNC helped to increase the tensile strength, Young's modulus, water resistance, and alignment of the fibers. In addition, these fibers were encapsulated with a model drug (riboflavin) and were found to be effective for controlled release within a period of 24 h [39].…”
Section: Enzymatic Production Of Nanocellulosementioning
confidence: 99%